“The Course Was Not Only for the Semester but Also for Life”: Scaffolding Summary Writing for EFL Students Across Academic Disciplines - Sjöberg-Hawke, Carina (Journal of Academic Writing, 2020)
It can be a challenge for a university teacher to arrange the teaching of written tasks so that weak foreign language students with differing disciplinary backgrounds can develop their written communication skills. The difficulty is to avoid the focus from becoming just language proficiency. In one course at a technical university in Sweden, three written summaries are scaffolded to address such a challenge. The purpose of this teaching practice paper is to show how employing a specific strategy of repetition facilitates the writing skill development in low-level English language multidisciplinary students. The repeated features are the genre of the task, the writing process used and the occurrences of teacher response. They are organised along a specific learning path so as to encourage the students to build on the knowledge gained in each iteration, between tasks and potentially beyond the course. The paper describes the journey the students take writing the three summaries, working on fulfilling criteria concerned with aspects such as content organisation, coherence and cohesion, and limited grammar errors. A brief analysis of excerpts from one case student’s first and third summaries is included. It is suggested that while the scaffolding can remain the same, the material could be replaced to suit other skills and language level needs.